Two new genera of Pteronemobiini crickets from the Brazilian Atlantic forest (Orthoptera, Grylloidea, Trigonidiidae, Nemobiinae) - Bolfarini, Marcio P. [UNESP]; Capellari, Renato P.; De Mello, Francisco De A. G. [UNESP] (Magnolia Press, 2012)
Two new genera and species of Pteronemobiini crickets (Grylloidea: Trigonidiidae: Nemobiinae) are described from southern Brazilian Atlantic Forest: Kevanemobius paulistorum gen. n. et sp. n., and Pepoyara jagoi gen. n. et sp. n. The position of these genera among other Pteronemobiini is briefly discussed. Copyright © 2012 Magnolia Press.
Keywords: Atlantic Forest; Grylloidea; Nemobiinae; New Taxa; Orthoptera; Pteronemobiini; South America